Стюардесса: роман / Елена Ласкарева - Ласкарева Елена Николаевна (АСТ, 2001)
Экземпляры: Ершовская библиотека (20191120) / Инвентарный номер: 7605 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Л 26 / ББК: 84(2Рос=Рус)6-44